Successful satellite population management: Girnar wildlife sanctuary as a habitat for Asiatic lions - Mohan Ram; Aradhana Sahu; Nityanand Srivastava; Lahar Jhala; Yashpal Zala; Meena Venkataraman (Global Ecology and Conservation)
Landscape-level approaches, such as integrating corridors with site-specific habitat conservation, are crucial for protecting endangered carnivores. This paper presents a case study of a satellite population conservation approach, focusing on the Girnar forests in Gujarat, India. The Girnar forests, located 35 km from the Gir National Park and Wildlife Sanctuary (PA), have served as a crucial satellite habitat for dispersing Asiatic lions (Panthera leo persica) since the late 1990s. Historically, the Gir-Girnar forests were part of a connected landscape, but agricultural expansion and development have fragmented this area into disconnected patches of wasteland, grasslands, and riverine corridors. The Greater Gir concept was aimed to create a ''safety-net'' by enhancing conservation management outside the Gir PA, connecting natural habitats across four districts to support dispersing lions. Improved management practices were implemented in the satellite habitats, culminating in the declaration of Girnar forests as a legally protected wildlife sanctuary in 2008. The paper evaluates the success of these efforts, highlighting improvements in habitat quality, prey availability, and resident lion populations. Data insights on habitat use, immigration, and emigration patterns from monitoring radio-collared lions are also discussed. Furthermore, the paper outlines future conservation actions to ensure the preservation of the Girnar Wildlife Sanctuary (178.80 km2), which has now transitioned from being a ‘sink’ to a ‘source’ habitat. Additionally, the paper addresses the challenges associated with maintaining a balance between preserving the region’s cultural heritage and ensuring the conservation of lions, both of which hold legitimate claims to historical territories.